(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Food allergens remain a serious health threat: gluten above 20 ppm triggers celiac disease, lactose over 0.1% causes intolerance in millions, and peanut protein even at 0.2 ppm can lead to anaphylactic shock. Traditional laboratory methods—ELISA for proteins, enzymatic kits for sugars, PCR for DNA—require separate tests, specialized equipment, several hours, and significant costs. Multisensor systems solve this problem radically: a single small sample (0.1–0.5 g) simultaneously passes through multiple analytical channels based on IR spectroscopy, spectrophotometry, and mass spectrometry, with artificial intelligence integrating the data to deliver a complete allergen profile in 10–30 seconds. This approach not only accelerates control but also makes it accessible in field conditions—from production lines to home kitchens.